Information Sharing Model among State Agencies in Malaysia: A Case Study - Ruslawati Nik Mustapa, Nik; Bt Haji Ibrahim, Huda; Bt Mohd Nadzir, Maslinda; ., . (International Journal of Engineering and Technology, 2018)
Information-sharing projects are becoming increasingly important in state agencies. Generally, organizations base their decision to move forward with an information-sharing project on the project’s expected benefits such as better services, operational savings, and increased program effectiveness. In Malaysia, currently, there is insufficient information  about the current practices, states or level maturity, requirements, models adopted in relation to information sharing for the e-services’ implementation among the government agencies. The paper explores the various dimension and stages of government information sharing in the context of Malaysia e- Government by using a framework of Government Information sharing framework adopted from the  Estevez, Fillottrani, and Janowski. In this study, An exploratory case study was used to identify problems and collect data in this study. The study results show that environmental, inter-organization, organization and  technological dimension influence information sharing within state agencies. It is also shown that waqf system is in Stage 1(experience sharing).  An extensive set of recommendations is put forth to enable state agency to move from Stage 1 to Stage 2.